A novel role for coinhibitory receptors/checkpoint proteins in the immunopathology of sepsis. Issue 6 (2nd February 2018) - Fallon, Eleanor A.; Biron‐Girard, Bethany M.; Chung, Chun‐Shiang; Lomas‐Neira, Joanne; Heffernan, Daithi S.; Monaghan, Sean F.; Ayala, Alfred
Abstract: Coinhibitory molecules, such as PD‐1, CTLA‐4, 2B4, and BTLA, are an important new family of mediators in the pathophysiology of severe bacterial and/or fungal infection, as well as the combined insults of shock and sepsis. Further, the expression of these molecules may serve as indicators of the immune status of the septic individual. Using PD‐1:PD‐L as an example, we discuss in this review how such checkpoint molecules may affect the host response to infection by mediating the balance between effective immune defense and immune‐mediated tissue injury. Additionally, we explore how the up‐regulation of PD‐1 and/or PD‐L1 expression on not only adaptive immune cells (e.g., T cells), but also on innate immune cells (e.g., macrophages, monocytes, and neutrophils), as well as nonimmune cells during sepsis and/or shock contributes to functional alterations often with detrimental sequelae. Abstract : Review of checkpoint proteins' contributions to immunological signaling in shock and sepsis.